A Study on Synthesis and Testing of Polyols Using Soybean Oil and Castor Oil - Khan, Shahzad Maqsood; Gull, Nafisa; Akram, Muhammad Yaseen; Haider, Hakim Ali; Akram, Muhammad Yasir; Imran, Muhammad; Butt, Muhammad Taqi Zahid; Jamil, Tahir (ASEAN Journal of Chemical Engineering, 2013)
The feasibility of methods of trans-esterification reactions for the preparation of polyols from unsaturated soybean oil and castor oil have shown in this study. The polyol products formed from soybean oil has primary alcohol functional group. For castor oil polyol, hydroxyl group of any chain of triglyceride is replaced by chlorine. Thus the polyol formed has two hydroxyl (-OH) groups. Polyol is identified from hydroxyl functional group using Fourier Transform Infrared Spectroscopy (FTIR), and characterized by acid value. It is seen that the synthesized polyols are useful in the treatment of processes, using polyols for the production of polyurethanes, and also manipulated to synthesize polyurethane with required properties.